Três catálogos de mostras de cinema - Nogueira, Calac (Imagofagia, 2021)
Sobre Almeida, Paulo Ricardo Gonçalves e Barros, Ana Rebel (org.). Francis Ford Coppola: O cronista da América (Rio de Janeiro: VOA!, 2015. ISBN: 978-85-67153-01-8). Murari, Lucas e Nagime, Mateus (org.). New Queer Cinema: Cinema, sexualidade e política (ISBN: 978-85-69488-00-2). Duarte, Theo e Mourão, Patrícia (org.). Cinema Estrutural (Rio de Janeiro: Aroeira, 2015. ISBN: 978-85-64615-02-1).